2013
DOI: 10.1126/scitranslmed.3004812
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxin A 4 Regulates Natural Killer Cell and Type 2 Innate Lymphoid Cell Activation in Asthma

Abstract: Asthma is a prevalent disease of chronic inflammation in which endogenous counter-regulatory signaling pathways are dysregulated. Recent evidence suggests that innate lymphoid cells (ILCs), including natural killer (NK) cells and type 2 innate lymphoid cells (ILC2), can participate in the regulation of allergic airways responses, in particular airway mucosal inflammation. Here, we have identified both NK cells and ILC2 in human lung and peripheral blood in healthy and asthmatic subjects. NK cells were highly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
502
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(519 citation statements)
references
References 52 publications
10
502
0
7
Order By: Relevance
“…Further, ILC2s have also recently been shown to respond directly to non-cytokine molecules, including eicosanoids. Specifically, ILC2s are activated by prostaglandin D 2 (PGD 2 ) (Barnig et al 2013;Chang et al 2013;Xue et al 2013) and leukotriene D 4 (LTD 4 ) and are inhibited by lipoxin A 4 (LXA 4 ) (Barnig et al 2013). In addition to activation, human ILC2s express the PGD 2 receptor chemoattractant receptor-homologous molecule expressed on T H 2 cells (CRTH2) and migrate in vitro in response to PGD 2 (Chang et al 2013;Xue et al 2013).…”
Section: Regulation and Effector Functions Of Ilc2smentioning
confidence: 99%
See 2 more Smart Citations
“…Further, ILC2s have also recently been shown to respond directly to non-cytokine molecules, including eicosanoids. Specifically, ILC2s are activated by prostaglandin D 2 (PGD 2 ) (Barnig et al 2013;Chang et al 2013;Xue et al 2013) and leukotriene D 4 (LTD 4 ) and are inhibited by lipoxin A 4 (LXA 4 ) (Barnig et al 2013). In addition to activation, human ILC2s express the PGD 2 receptor chemoattractant receptor-homologous molecule expressed on T H 2 cells (CRTH2) and migrate in vitro in response to PGD 2 (Chang et al 2013;Xue et al 2013).…”
Section: Regulation and Effector Functions Of Ilc2smentioning
confidence: 99%
“…A recent study has shown that TSLP can contribute to ILC2 activation that promotes corticosteroid resistance in the context of IL-33-mediated airway inflammation (Kabata et al 2013). Further, recent reports suggest that other factors, such as eicosanoids, could also play a key role in promoting ILC2 responses in the inflamed lung (Barnig et al 2013;Doherty et al 2013). For instance, lung ILC2s express the receptor for LTD 4 and ligation of this receptor rapidly induces IL-5 production by ILC2s.…”
Section: Ilc2s and Allergic Airway Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the leukotriene inhibitor montelukast can inhibit cytokine production by both mouse and human ILC2 (52,54), suggesting that part of the therapeutic effect of this drug in asthma may be due to blocking ILC2 activation. Notably, human ILC2 also express the pro-resolvin receptor ALX/FRP2, which binds the resolving lipoxin A 4 (51). Like leukotrienes and prostaglandins, lipoxin A 4 is derived enzymatically from arachidonic acid.…”
Section: Ilc2 In Skin Allergymentioning
confidence: 99%
“…En outre, des essais cliniques de blocage de l'IL-13 par un anticorps monoclonal, menés chez des patients asthmatiques, ont montré une efficacité relative [18]. Les ILC1 (NK) et les ILC2 pourraient également intervenir dans l'asthme via l'induction de l'apoptose des éosinophiles par les NK et la production d'IL-13 par les ILC2, ces deux mécanismes étant régulés par la lipoxine A4 [19]. Le rôle des ILC2 dans la progression de ces pathologies reste néanmoins à déterminer.…”
Section: Les Ilc2 Chez L'hommeunclassified